STUDI EMISI KARBON DIOKSIDA DARI TIGA JENIS LAHAN GAMBUT DI DESA TANJUNG LEBAN DAN SEPAHAT KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Edo Furnando; Tengku Ariful Amri; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The high concentration of carbon dioxide in the atmosphere is suspected as the main cause of global warming, therefore, the carbon balance is very important to investigate. At this time, tropical peatlands are used as agricultural cultivation and plantation, one of them is in Bengkalis, Riau Province. This study aimed to measure the concentration of CO2 based on the relationship of physical and chemical properties of peat. Measurements were performed on peatlands which have different vegetation cover, i.e. bush land, oil palm plantation, and secondary forest. The used method in this study are Infrared Gas Analyzer and Gas Chromatography. The average of obtained emissions based on the effect of water table, peat temperature, and pH (H2O) of bush land, oil palm plantation, and secondary forest are 497,4 ppm, 523,2 ppm, and 457,2 ppm, respectively.